Effect of oregano essential oil and ozonation as an alternative for shelf-life extension in cooked beans (Phaseolus vulgaris L.) - Yanchaliquin Yanchaliquin, Adriana Geovanna; Romero Corral, Romero Corral (ACI Avances en Ciencias e Ingenierías, 2026)
The objective of this study was to evaluate the efficacy of combining oregano essential oil (AOE), and ozone in extending the shelf life of cooked beans (Phaseolus vulgaris L.), using an AxB factorial design: a control (T0), and four combinations of ozone (0.25 and 0.50 ppm), with AOE (0.30 % and 0.50 %), for 21 days of storage at 4°C. The beans were hydrated (3:1 water: bean), cooked for 90 minutes, cooled with ozonated water, coated with AOE emulsifier in 0.5 % Tween 80, and packaged in polyamide and polyethylene bags. Physicochemical parameters (pH and acidity), microbiological parameters (mesophilic aerobes, total coliformes, Escherichia coli, Staphylococcus aureus, and Salmonella spp.), and sensory attributes (color, odor, flavor, texture, and acceptability) were evaluated. ANOVA and Tukey’s test were applied (p < 0.05). There were statistically significant differences (p < 0.001), between treatments and control during storage. T3 presented the lowest acidity (0.08 g/100 g), and the control the highest (0.17 g/100 g). T0, T1 and T2 maintained slightly acidic pH (5.2–5.5), T3 and T4 exceeded pH 7.0. T3 achieved the greatest microbial reduction in mesophilic aerobes (1.37 log₁₀ CFU/g), and total coliforms (2.60 log₁₀ CFU/g), differing significantly from the control. Sensorially, T3 obtained the highest scores in all attributes until day 21. It is concluded that the joint application of ozone and AEO, especially in T3, represents a viable and effective technological alternative to preserve the physicochemical, microbiological and sensory quality of cooked beans.